Antifungal Combination Therapy for Invasive Fungal Infections in Pediatric Leukemia Patients: An Observational Cohort Study - Saliha Kanık Yüksek; Aslınur Özkaya Parlakay; Belgin Gülhan; Neşe Yaralı; Namık Yaşar Özbek; Hasan Tezer (Galenos Publishing House, 2023)
Objective: The role of combination regimens in the treatment of invasive fungal infections (IFIs) in hematologic malignancies remains unclear. We aimed to demonstrate data about combined antifungal therapy (CAT) in pediatric leukemia patients with IFI. Method: Between January 2014 and December 2018, a total of 33 IFI episodes in 28 leukemia patients were analyzed retrospectively. Results: The study patients had acute lymphoblastic leukemia (n=19), acute myeloblastic leukemia (n=9), leukemia relapse (n=21; 75%) and remission (n=7; 25%). The patients were classified as having possible (n=26; 78.8%), probable (n=5; 15.1%) and proven IFI (n=2; 6.1%). Liposomal amphotericin B (LamB) was the most preferred agent (50%) in monotherapy. Mean duration of monotherapy was 12.84+-4.28 (5-24) days. LamB plus voriconazole (54.5%) was the most commonly preferred CAT. Mean duration of CAT was 42.36+-36.4 days, and this combination regimen was not changed throughout the treatment period (p=0.571). Total and IFI-related mortality rates were 60.7% vs 46.4%, respectively. Mortality rates were significantly higher in patients with relapse (p=0.006). Complete response was obtained in 81.8% of surviving patients. Side effects of CAT were observed at quite a low level. Conclusion: CAT has been found to be safe in the treatment of IFI episodes of pediatric leukemia. Uncontrolled underlying disease is the most important factor affecting the mortality rates in IFI.